The Correlation Between Perception And Behavior Of River Pollution By Communities Around Brantas Riverbank In Malang - Kuni Mawaddah; Sueb Sueb (UPT Penerbitan Universitas Jember, 2016)
Water is the most important element of the natural resources so that water pollution is a serious threat to thewell-being of the earth and its inhabitants. River water as a source of important functions in the community is needed buthuman can cause water pollution. The purposes of this study are to determine the public perception of maintainingcleanliness, pollution behavior in the Brantas riverbasin, and the relationship between perception and behavior. The methodused is a closed interview in accidental sampling technique. The respondents are people who live in the Brantas riverbank,Malang. Data were tested using Spearman correlation test because the data were not normally distributed. Spearmancorrelation of test results obtained significance value of 0.996 means that the public perception does not correlate with thebehavior of pollution in the Brantas River basin. Conclusions of this research are that public perception agree maintainingcleanliness, communities near Brantas riverbank often behave to pollute the river, and there is no correlation between theperception and behavior of river pollution by communities around the Brantas riverbank in Malang.